Perancangan Integrasi Sistem Enkripsi dan Steganografi untuk Pengamanan Data Suara Manusia Berbasis Web - Maheswara, A.A Putu Priyamdeva Arya; Sasmita, Gusti Made Arya; Wiranatha, A.A Ketut Agung Cahyawan (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 5 No 1 (2024): JITTER, Vol.5, No.1, April 2024DO - 10.24843/JTRTI.2024.v05.i01.p02, 2024)
Audio steganography on images is a method used to secretly hide audio messages in images. The Least Significant Bit (LSB) method is also combined with Advanced Encryption Standard (AES) to increase the security of confidential messages. Audio messages that you want to keep secret can be encrypted using Advanced Encryption Standard (AES) before being inserted into the image. Advanced Encryption Standard (AES) can be combined with the use of Rivest Shamir Adleman (RSA) on Advanced Encryption Standard (AES) keys. Rivest Shamir Adleman (RSA) is used to increase the security of Advanced Encryption Standard (AES) keys. The Advanced Encryption Standard (AES) key can be encrypted using Rivest Shamir Adleman (RSA) before being inserted into the image using the Least Significant Bit (LSB) Method, so that only recipients who have the Rivest Shamir Adleman (RSA) key are suitable for accessing the audio message. kept secret. The results of this processing can be measured from the PSNR (Peak-Signal-to-Noise Ratio) figure.